Atypical negative pressure pulmonary edema after extracorporeal membrane oxygenation therapy for COVID‐19. Issue 1 (8th December 2022) - Suzuki, Yu; Ogoshi, Takaaki; Taura, Yusuke; Oda, Shiori; Uchiyama, Daiji; Ueda, Hiroyuki; Yatera, Kazuhiro
Key message: NPPE imaging findings were reported to show a preferential central and nondependent distribution. However, in our case, NPPE showed a peripheral accent pattern, resembling the ARDS pattern of COVID‐19 pneumonia 4 months ago. Capillary damage from COVID‐19 might still exist. Abstract : Atypical negative pressure pulmonary edema showing a peripheral accent pattern resembling ARDS has emerged after COVID‐19 pneumonia four months ago. Capillary damage from COVID‐19 might still exist.